One-pot Pseudo-Domino Three-Component Knoevenagel Condensation Reaction in Water Enabled by Micellar Catalyst: Mechanism and Reactivity - Ahanthem, Dini; Ojha, Devi P.; Chipem, Francis A.S.; Laitonjam, Warjeet S. (Letters in Organic Chemistry, 2020)
The micellar catalysis is well-known for its hydrophobic effect that is the tendency of nonpolar groups to cluster within the lipophilic core so as to shield them from contact with an aqueous environment formed upon the dissolution of a surfactant in water. This provides a unique opportunity to establish organic transformations in greener solvents, such as water leading to organic waste control and easy product isolation protocols. Considering the significant interaction of thiobarbituric acid moieties in a biological macromolecule core, herein, a highly efficient procedure for the synthesis of biological and medicinal important 5-(arylmethylene)dihydro-2-thioxo-4,6(1H,5H)-pyrimidinediones via Knoevenagel condensation of thiobarbituric acids and aldehydes catalyzed by a surfactant, sodium dodecyl sulfate, is developed. The synthetic procedure shows the excellent activity of the micellar catalysts towards the aldehyde activation leading to a facile condensation. The application of the method is demonstrated by further synthesis of 5,5'-(4-arylmethylene)bis[dihydro-2-thioxo-4,6(1H,5H)- pyrimidinediones]. Theoretical studies of the reaction were also carried out to investigate the effect of electron releasing and electron-withdrawing group in benzaldehyde on the reaction.
Keywords: recyclability